2005
DOI: 10.1021/ol0518840
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Marine Sponge Derived β2-Adrenoceptor Agonist S1319

Abstract: [reaction: see text] The marine sponge derived beta2-adrenoceptor agonist S1319 has been synthesized following a six-step linear sequence. Central to the approach employed is the formation of a 7-lithiated-2,4-dialkoxybenzothiazole intermediate obtained via a directed-lithiation/benzyne-mediated cyclization reaction. The incorporation of a tert-butyl ether residue into the cyclization precursor for the pivotal ring-closing step has been shown to significantly increase the efficiency of the reaction by the supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…387 An adrenaline analogue, S1319 originally isolated from a Dysidea species, 388 This journal is © The Royal Society of Chemistry 2007 has been synthesised. 389 An alkyl pyridinium dimer 373 with agonist activity against chemokine receptor CXCR3 was isolated from an unidentified sponge (Bahamas). 390 The battle over determining the true structure of pyrinodemin A rages on.…”
Section: Spongesmentioning
confidence: 99%
“…387 An adrenaline analogue, S1319 originally isolated from a Dysidea species, 388 This journal is © The Royal Society of Chemistry 2007 has been synthesised. 389 An alkyl pyridinium dimer 373 with agonist activity against chemokine receptor CXCR3 was isolated from an unidentified sponge (Bahamas). 390 The battle over determining the true structure of pyrinodemin A rages on.…”
Section: Spongesmentioning
confidence: 99%
“…8,9 As previously, a benzyne-mediated cyclisation-reaction of the 3-fluorophenyl thiocarbamate derivative 7 gave the 7-lithiated benzothiazole intermediate 8, which could be acylated directly at À40°C with the Weinreb amide of chloroacetic acid 9 to give 10. In contrast to the earlier route, under these conditions no transmetalation step was required to modulate the basicity of 8, and this transformation could be run reliably on a multi-kilogram scale.…”
Section: Introductionmentioning
confidence: 81%
“…[232][233][234] S1319 was rst characterized as novel adrenaline derivative with potent bronchodilator activity; the structure was determined on the basis of its spectroscopic data. 234 Synthesis has been achieved in racemic form 235 without disclosure of the absolute stereochemistry at the secondary alcohol. 176 binds to b1and b2adrenergic receptors and relaxes guinea-pig tracheal smooth muscle as potently as the clinically used anti-asthmatic b2 agonist formoterol, albeit with shorter duration.…”
Section: Other Synaptic Gpcrs and Transportersmentioning
confidence: 99%
“…Inhibition of GSK-3b by 230 was selective over other related kinases, and docking analysis suggested that 230 binds to a site distinct from the ATP binding site but not that targeted by manzamines. 289 Carteriosulfonic acids A-C (233)(234)(235), isolated from a Carteriospongia sp. sponge collected in the Philippines, also inhibited GSK-3b, potentially through an allosteric mechanism.…”
Section: Kinase Modulatorsmentioning
confidence: 99%